Floral visitors of three species of Corallorhiza in Monte Tláloc, Texcoco, Estado de México, México - Téllez Baños, Bruno Enrique; Gomez Escamilla, Ivonne Nayeli; Navarrete Jiménez, Alejandro; Espejo Serna, Adolfo 1951-; López Ferrari, Ana Rosa 1957- (2023)
Corallorhiza is a genus of mycoheterotrophic orchids that includes 12 species, most of them re-stricted to North and Central America. In Mexico, there are seven taxa, distributed throughout the country, except for seven of the 32 Mexican states; in Estado de México all of them are present. The Orchidaceae is known for its diversity of pollination syndromes; however, for the more than 200 species of mycoheterotrophic orchids, little has been studied about their floral visitors and pollinators, and for the Mexican species of Corallorhiza nothing is known to date. Our goal was to document photographically and identify all the floral visitors of three sympatric species of the genus in Monte Tláloc, municipality of Texcoco, Estado de México. We observed individuals of Araneae, Coleoptera, Diptera, Hemiptera, and Hymenoptera visiting flowers of Corallorhiza macrantha, C. macrantha × C. maculata, C. maculata, and C. striata. Only Ocyptamus coeru-leus and Platycheirus sp. (Diptera: Syrphidae) were found carrying pollinaria on their thorax. These are the first records of potential pollinators for the genus Corallorhiza in Mexico.
Corallorhiza es un género de orquídeas micoheterótrofas que comprende 12 especies, la mayoría de ellas restringidas a Norte América y Centroamérica. En México habitan siete de ellas que se distribuyen en todo el país, excepto en siete de los 32 estados; en el Estado de México están todas presentes. Orchidaceae es conocida por su diversidad en síndromes de polinización; sin embargo, para las más de 200 especies de orquídeas mi-coheterótrofas poco se ha estudiado sobre sus visitantes florales y polinizadores, y para el caso de las especies de Corallorhiza mexicanas nada se conoce. Nuestro objetivo fue documentar fotográficamente e identificar a todos los visitantes florales de tres especies simpátricas del género en el Monte Tláloc, municipio de Texcoco, Estado de México. Observamos individuos de Araneae, Coleoptera, Diptera, Hemiptera e Hymenoptera en las flores de Corallorhiza macrantha, C. macrantha × C. maculata, C. maculata y C. striata. Únicamente Ocyptamus coeruleus y Platycheirus sp. (Diptera: Syrphidae) fueron encontrados transportando polinias en el tórax. Éstos son los primeros registros de polinizadores potenciales para el género Corallorhiza en México.
Keywords: RAÍZ DE CORAL -- MÉXICO; ORQUÍDEAS -- POLINIZACIÓN -- MÉXICO; DIPTEROS; COLEOPTEROS; HEMIPTEROS; HYMENOPTEROS